Pengetahuan Wanita Usia Subur Sebelum dan Sesudah Diberikan Penyuluhan Tentang Pemeriksaan Payudara Sendiri Di Desa Suka Maju Kecamatan Tambusai Kabupaten Rokan Hulu. - Handayani, Eka Yuli; Sepduwiana, Heny; Wahyuny, Romy (Jurnal Martenity and Neonatal, 2019)
In Indonesia based on global data on the Burden of Cancer (Globocan), breast cancer is the most cancer in women (26 per 100,000) followed by uterine cancer (16 per 100,000). Hospital system data (SIRS) 2007 showed that the incidence of breast cancer reached 21.69% higher than cervical cancer, which was 17%. Be aware that breast self-examination aims to determine whether there is cancer in a woman's breast. This examination is used by using a mirror and carried out by women aged 20 and above. Breast cancer is a malignant neoplasm that has a very broad spectrum and complex. Almost no cancer can be cured spontaneously. Every 11 minutes there is one world population who dies of cancer, every 3 minutes there is one new cancer sufferer. This study aims to determine the relationship of counseling to the knowledge of women of childbearing age about BSE examination. The research method used is quantitative with One group pretest posttest approach. The study was conducted in Suka Maju Village in July 2017. The samples of this study were 75 people. Data collection in this study uses primary data, namely using questionnaires. Data were analyzed using t-test analysis.